The Arab Spring and Arab thaw unfinished revolutions and the quest for democracy - Davis, John (Ashgate Pub., 2013)
The Arab Spring and Arab Thaw examines a range of successful and unsuccessful protest strategies and counter revolutionary tactics employed by protestors and autocratic regimes. Contributors explore the reactions of the USA.